Vascular brachytherapy versus drug‐eluting stents in the treatment of in‐stent restenosis: A meta‐analysis of long‐term outcomes. Issue 2 (11th May 2015) - Benjo, Alexandre; Cardoso, Rhanderson N.; Collins, Tyrone; Garcia, Daniel; Macedo, Francisco Y.; El‐Hayek, Georges; Nadkarni, Girish; Aziz, Emad; Jenkins, J. Stephen
Abstract : Introduction: Clinical trials have shown a short‐term benefit of drug‐eluting stents (DES) compared to vascular brachytherapy (VBT) for treatment of in‐stent restenosis (ISR). The long‐term benefits of DES vs. VBT are conflicting in the literature. This study aimed to do a meta‐analysis of long‐term outcomes of DES compared to VBT for treatment of ISR. Methods: PubMed, EMBASE, Cochrane Central and unpublished data were searched for cohort studies and randomized controlled trials (RCTs) that directly compared VBT to DES for the treatment of ISR. We evaluated the following outcomes at 2–5 years of follow‐up: target lesion revascularization (TLR), target vessel revascularization (TVR), myocardial infarction (MI), stent thrombosis, cardiovascular (CV) mortality, and overall mortality. Heterogeneity was defined as I 2 values > 25%. Review Manager 5.1 was used for statistical analysis. Results: We included 1, 375 patients from five studies, of which three were RCTs. VBT was used to treat ISR in 685 (49.8%) patients. After a 2–5 year follow‐up, no significant differences were found between treatment groups regarding MI ( P = 0.49), stent thrombosis ( P = 0.86), CV mortality ( P = 0.35), and overall mortality ( P = 0.71). TLR (OR 2.37; CI 1.55–3.63; P < 0.001) and TVR (OR 2.23; CI 1.01–4.94; P = 0.05) were significantly increased in patients who received VBT. Conclusion: This study suggests that DES are associated with decreased long‐term revascularization procedures when compared to VBT for the treatment of ISR. This benefit does not appear to be associated with a significant reduction in mortality or myocardial infarction. © 2015 Wiley Periodicals, Inc.